2019
DOI: 10.1186/s12902-019-0473-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sexual dysfunction and related factors among diabetes mellitus patients in Southwest Ethiopia

Abstract: BackgroundDiabetes mellitus causes multiple medical, psychological and sexual problems in both men and women. Sexual dysfunction is one of those problems that lead to a strong social and psychological problem which adversely affect marital relation and treatment outcome. The issue has not been well studied in Ethiopia; therefore, this study aimed to evaluate the prevalence and factors related to sexual dysfunction in adult patients with diabetes mellitus.MethodsFacility-based cross-sectional study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 31 publications
4
51
0
3
Order By: Relevance
“…Of these reports, only those that described the data in terms of the odds ratio, relative risk and categorical variables were included, therefore eight cross -sectional studies were included. In the present analysis, the pooled effect of eight studies [31] , [47] , [51] , [52] , [54] , [57] , [58] , [60] showed that being over 40 years was statistically associated with ED in patients with DM (OR = 1,24; 95%CI; 1.03, 1.51). The heterogeneity test (I 2 = 90%) showed significant evidence of variation across studies.…”
Section: Review Findingsmentioning
confidence: 62%
See 2 more Smart Citations
“…Of these reports, only those that described the data in terms of the odds ratio, relative risk and categorical variables were included, therefore eight cross -sectional studies were included. In the present analysis, the pooled effect of eight studies [31] , [47] , [51] , [52] , [54] , [57] , [58] , [60] showed that being over 40 years was statistically associated with ED in patients with DM (OR = 1,24; 95%CI; 1.03, 1.51). The heterogeneity test (I 2 = 90%) showed significant evidence of variation across studies.…”
Section: Review Findingsmentioning
confidence: 62%
“…Five of the studies included in this review were from Nigeria [46] , [47] , [48] , [49] , [50] , four from Ethiopia [51] , [52] , [53] , [54] , three from Ghana [32] , [55] , [56] , one each from South Africa [57] , Egypt [31] , Kenya [58] , Zimbabwe [59] , and Tanzania [60] . Concerning the sampling technique 12 of the studies [31] , [32] , [46] , [47] , [48] , [49] , [50] , [54] , [55] , [56] , [58] , [59] used consecutive sampling to select study participants. However, one study [60] did not report the sampling method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies were published between 2010 8 and 2020. 16 Of the included studies, three were conducted in Oromia, 8,15,16 two in the Amhara region 9,18 (one from the grey literature), and one in the Tigray region. 17 Except for the study from Mizan-Tepi 15 with a response rate of 94%, the response rate of the remaining five studies was 100%.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…17 Except for the study from Mizan-Tepi 15 with a response rate of 94%, the response rate of the remaining five studies was 100%. 8,9,[16][17][18] The mean age of patients in the six studies included in this systematic review and meta-analysis ranged from 41.76 (AE9.00) years 15 to 54.12 (AE16.51) years. Regarding assessment tools of ED, four studies 9,[16][17][18] (the Gondar study was from the grey literature) used the International Index of Erectile Function (IIEF-5), and one study used the 14-item Sexual Functioning Questionnaire (CSFQ-14).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%